Hortasa (2020)
Hortasa offers vegetables at home so it is a service and product that aims to bring consumers closer to agricultural activities through a series of established dynamics that occur both on the El Refugio farm and in the trailer, which serves as a channel to ensure that all promises of value are delivered to both customers and the producer. Hortasa is an exclusive service for the sector adjacent to the production area, which guarantees freshness and immediacy.